General health and related factors in employed nurses in Medical-Educational Centers in Rasht - Shahrokh Maghsoodi; Masoumeh Hesabi; Abdolhosein Emami sigaroudi; Ehsan Kazemnejad leili; Arezou Monfared (Journal of Holistic Nursing and Midwifery)
Abstract